Dimensionality and Psychometric Properties of the Spanish version of the Mechanisms of Moral Disengagement Scale (MMDS-S) - Rubio-Garay, Fernando; Amor, Pedro J.; Carrasco, Miguel A. (Revista de Psicopatología y Psicología Clínica, 2017)
Abstract: This study examines the dimensions and psychometric properties of the Spanish version of the Mechanisms of Moral Disengagement Scale (MMDS). The MMDS was designed to evaluate the moral disengagement construct. A sample of 513 students was assessed (58.3% females; 15 to 25 years-of-age). Confirmatory factor analysis showed four models with an adequate fit, both for a first-order factorial structure (Model 1) and a second-order factorial structure (Models 2, 3 and 4). Model 4 achieved the best fit indices [χ2 = 19.35; RMSEA = .016; GFI = .99; AGFI = .98; ECVI = .11; CAIC = 156.92], a model represented by a general second-order factor (moral disengagement) with three fi rst-order dimensions: disengagement by depersonalization; disengagement by irresponsibility; and disengagement by rationalization. Moreover, significant relations between moral disengagement, aggression, and empathy were found. This scale appears a reliable and valid instrument to evaluate the moral disengagement in adolescents and young adults. Resumen: Dimensiones y propiedades psicométricas de la versión española de la Escala de Mecanismos de Desconexión Moral (MMDS). Este trabajo analiza las dimensiones y propiedades psicométricas de la versión española de la Escala de Mecanismos de Desconexión Moral (MMDS). Este instrumento fue diseñado para evaluar el constructo desconexión moral. Se evaluaron 513 estudiantes (58.3% mujeres; rango de 15-25 años). El análisis factorial confirmatorio mostró cuatro modelos con un adecuado ajuste y una estructura factorial de primer orden (Modelo 1), y una estructura de segundo orden (Modelos 2, 3 y 4). El Modelo 4 ofreció el mejor ajuste [χ2 = 19.35; RMSEA = .016; GFI = .99; AGFI = .98; ECVI = .11; CAIC = 156.92], representado por un factor general de segundo orden (desconexión moral) y tres de primer orden: desconexión por despersonalización; desconexión por irresponsabilidad; y desconexión por racionalización. Se encontraron relaciones significativas entre la desconexión moral, la agresión y la empatía. El instrumento es válido y fiable para evaluar la desconexión moral en adolescentes y adultos jóvenes.